Defeasible decision making in a robotic environment - Ferretti, Edgardo (2007)
Decision making models for autonomous agents are recently receiving increased attention, particularly in the feld of intelligent robots. This work presents a Defeasible Logic Programming approach to decision making in an environment with single and multiple robots. We will show, how a successful tool for knowledge representation and defeasible reasoning could be applied to the problem of deciding which task should be performed next. Besides, we will explain with detailed examples how the decision process is performed when there is only one robot in the environment, and then we will consider how the same robot decides when there are more robots working in the environment.